Cost-Effectiveness Study of Difamilast 1% for the Treatment of Atopic Dermatitis in Adult Japanese Patients - Takeshi Nakahara; Shinichi Noto; Miyuki Matsukawa; Hiroe Takeda; Yilong Zhang; Tomohiro Kondo (Adis, Springer Healthcare, 2024)
Abstract Introduction Difamilast has proven to be an effective treatment for the treatment of atopic dermatitis (AD) in Japan, but its cost-effectiveness remains unknown. Therefore, the objective of the current study was to determine the cost-effectiveness of difamilast 1% compared with delgocitinib 0.5% in Japanese adult patients with moderate-to-severe AD and compared with placebo in Japanese adult patients with all-severity AD from a Japanese public health-care perspective. Methods The analysis was conducted using a cost-effectiveness model from the Japanese public health-care perspective. This model had four health states ("clear," "mild," "moderate," and "severe") defined according to the Eczema Area and Severity Index score. The time horizon of the analysis was 1 year. Because the analysis period was short, no discount rate was applied. The proportions of patients previously estimated by the anchored matching-adjusted indirect comparison were implemented in the model. The model was further populated with data from the literature. The main model outcomes were quality-adjusted life-years (QALY), costs, and outcomes, including the incremental cost-effectiveness ratio. All prices were stated in JPY at the price level from 2018 April to 2019 March. One-way sensitivity analysis and probabilistic sensitivity analysis (PSA) were performed to assess the robustness of the results. Results In the base case, the cost-effectiveness of difamilast 1% compared with delgocitinib 0.5% and placebo was JPY 827,054/QALY and JPY 1,518,657/QALY, respectively. The PSA showed that the cost-effectiveness of difamilast 1% compared with delgocitinib 0.5% and placebo had a 66.6% and 99.6% probability of being below the JPY 5 million/QALY threshold, respectively. Conclusion The results suggest that difamilast 1% is a more cost-effective treatment option compared with delgocitinib 0.5% in Japanese adult patients with moderate-to-severe AD and compared with placebo in adult patients with all-severity AD from a Japanese public health-care perspective.